2001
DOI: 10.1007/bf02345364
|View full text |Cite
|
Sign up to set email alerts
|

Estimation and significance testing of cross-correlation between cerebral blood flow velocity and background electro-encephalograph activity in signals with missing samples

Abstract: Cross-correlation between cerebral blood flow (CBF) and background EEG activity can indicate the integrity of CBF control under changing metabolic demand. The difficulty of obtaining long, continuous recordings of good quality for both EEG and CBF signals in a clinical setting is overcome, in the present work, by an algorithm that allows the cross-correlation function (CCF) to be estimated when the signals are interrupted by segments of missing data. Methods are also presented to test the statistical significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…In previous work [8], we had found that there is low, but statistically significant cross-correlation between mean CBFV and the power of the EEG signal during TA activity in the newborn. There are sound physiological reasons why such correlation might be expected, given our understanding of cerebral blood flow control [1].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In previous work [8], we had found that there is low, but statistically significant cross-correlation between mean CBFV and the power of the EEG signal during TA activity in the newborn. There are sound physiological reasons why such correlation might be expected, given our understanding of cerebral blood flow control [1].…”
Section: Discussionmentioning
confidence: 99%
“…The set of signals used are the same as in the previous work [8]. A group of nine normal newborns (gestational age 37-41 weeks, Apgar at 1 and 5 min) were studied within seven days of birth (six of them within the first three days), after written informed parental consent and with approval of the local ethics committee (Instituto Fernandes Figueira, Fiocruz, Rio de Janeiro, Brazil).…”
Section: A Data Acquisition and Preprocessingmentioning
confidence: 99%
See 3 more Smart Citations